Testing models of care for terminally ill people who live alone at home: is a randomised controlled trial the best approach?. (11th October 2012) - Aoun, Samar M.; O'Connor, Moira; Breen, Lauren J.; Deas, Kathleen; Skett, Kim
Abstract This project implemented and evaluated two models of care for terminally ill people living alone at home: installing personal alarms (PA) and providing extra care aide (CA) support. The primary aim was to assess the feasibility of using a randomised controlled trial (RCT) approach with this group. A secondary aim was to assess the potential impact of the models of care on the participants' quality of life, symptom distress, anxiety and depression, and perceived benefits and barriers to their use. The two models of care were piloted in collaboration with Silver Chain Hospice Care Service (SCHCS) in Western Australia during 2009–2010. Using a pilot RCT design, equal numbers of participants were randomised to receive extra CA time, PAs or standard care. Attrition reduced the sample size from 20 in each group to 12, 14 and 17 respectively. The intervention period was between 6 and 12 weeks depending on prognosis. The participants were functionally and psychologically well and the majority lived alone by choice. There were physical and psychological benefits associated with provision of the two models of care, particularly for the group supported by CAs in terms of improved sleeping and appetite. However, the impact was mostly not statistically significant due to small sample sizes. The study has highlighted two methodological challenges: the wide variation in the degree of living alone at home leading to complex inclusion criteria, and an RCT approach with attrition differing across groups and patients not wanting to be included in the assigned group. The RCT approach is not considered appropriate for the 'home alone' palliative care population that would have been better supported by providing each participant with a personalised model of care according to needs. However, the outcomes of the project have prompted changes in SCHCS practice when providing care to these patients.